Correlation between Choroidal Neovascularization Shown by OCT Angiography and Choroidal Thickness in Patients with Chronic Central Serous Chorioretinopathy - Joanna Gołębiewska; Joanna Brydak-Godowska; Joanna Moneta-Wielgoś; Monika Turczyńska; Dariusz Kęcik; Wojciech Hautz (Journal of Ophthalmology)
Purpose. To assess the occurrence of choroidal neovascularization (CNV) secondary to chronic central serous chorioretinopathy (CSCR) using optical coherence tomography angiography (OCTA) and correlate these findings with choroidal thickness (CT). Materials and Methods. This retrospective study included 25 consecutive patients (43 eyes), mean age 48.12 ± 7.8 years, diagnosed with persistent CSCR. All patients underwent a complete ophthalmic examination, fluorescein angiography (FA), indocyanine green angiography (ICGA), optical coherence tomography, and OCTA. Results. CNV was confirmed in 18.6% of eyes using FA and ICGA and in 25.6% of eyes using OCTA. All cases of CNV were associated with irregular retinal pigment epithelial detachment. CT was increased in the affected eyes (mean 491.05 ± 91.98), but there were no statistically significant correlations between CT and CNV and PED occurrence (p=0.661 and p=0.614, resp.) and between CT and duration of the disease (p=0.940). Conclusions. OCTA detected CNV more frequently than other imaging modalities. CNV coexisted with irregular PED in all cases. CT was increased in eyes with chronic CSCR, but without any correlation with CNV occurrence; therefore, CT cannot be considered as a predictor of CNV occurrence. Further studies with a larger number of patients are needed to confirm these findings.